Is preterm delivery still related to physical working conditions in pregnancy?. Issue 1 (March 1991) - Saurel-Cubizolles, M J; Subtil, D; Kaminski, M
Abstract : STUDY OBJECTIVE--The aim was to determine the relationship between working conditions during pregnancy, women's occupation, and preterm birth. DESIGN--This was a retrospective survey. SETTING--The study was carried out in four public maternity units in France in 1987 and 1988. SUBJECTS--1949 women were interviewed after the delivery during their stay in hospital. Of these, 1002 held a job during pregnancy, but this report is confined to 875 women who had a single live birth and who had worked for more than the first trimester of pregnancy. MEASUREMENTS AND MAIN RESULTS--Information about social and occupational status was obtained through interviews, and data about gestational length were obtained from medical records. The primary results showed that preterm birth did not vary significantly according to working conditions whereas it differed according to occupational group. CONCLUSIONS--Occupation, but not working conditions, affected the incidence of preterm birth. This result is discordant with other studies which underlined the excess of preterm births among women with strenuous working conditions. Reasons for this discrepancy may include (1) change in perception of "strenuous working conditions"; (2) improved working conditions; (3) the development of "preventive" strategies by pregnant women. Occupation is a more reliable indicator of risk than self described working conditions.